2015
DOI: 10.1002/adem.201500380
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Gas Separation through Amorphous Silicon Oxycarbide Membranes

Abstract: Polymer-derived amorphous silicon oxycarbide (SiOC) ceramics are designed for hydrogen separation at high temperatures. To form amorphous SiOC top-coating with the thickness of about 300 nm, tubular porous g-Al 2 O 3 /a-Al 2 O 3 substrates with gradient porosity are threefold coated by vinylfunctionalized polysiloxane and pyrolyzed at 700 C under argon. N 2 -physisorption measurement confirms formation of microporous material with a specific surface area of about 400 m 2 g -1 . Single gas permeance characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…10 and 320, respectively). The experimental gas permeance data were rationalized using solid‐state diffusion (as for He and H 2 ) and gas translational diffusion (for CO 2 and SF 6 ) mechanisms . It was found that microporous SiOC membranes possess higher permeance for hydrogen than that reported for silica membranes.…”
Section: Properties Of Siocmentioning
confidence: 99%
“…10 and 320, respectively). The experimental gas permeance data were rationalized using solid‐state diffusion (as for He and H 2 ) and gas translational diffusion (for CO 2 and SF 6 ) mechanisms . It was found that microporous SiOC membranes possess higher permeance for hydrogen than that reported for silica membranes.…”
Section: Properties Of Siocmentioning
confidence: 99%
“…
Porous substrates play a major role in devices requiring the flow of fluids such as in filters and membranes. Porous substrates are also extensively used for the preparation of inorganic membranes for microfiltration, [1][2][3] desalination, [4][5][6][7] gas separation, [8][9][10][11] and percrystallization processes. [12,13] These inorganic membranes are known as asymmetric membranes as they are conventionally prepared by coating ceramic [14][15][16] or carbon [17][18][19] thin films as top layers on porous substrates.
…”
mentioning
confidence: 99%
“…The membrane thickness (L) was 50 nm as obtained from the SEM image shown in Fig. 2 and jump distance (d) was 0.8 nm which was used by following previous reports [39,45]. The calculated permeances of He and H2 were well consistent with experimental data, so that the solid-state diffusion model fitting analysis was to be made appropriately.…”
Section: Analysis Of Gas Permeation Behaviors (1) He and H2 Permeationsmentioning
confidence: 77%
“…The fitting parameters obtained in this study were listed in Table 2, and compared with those for H2-selective amorphous ceramic membranes previously reported by other research groups: polysiloxanederived amorphous silicon oxycarbide (SiOC) membrane (#01) synthesized by pyrolysis at 700 • C in Ar [45], and CVD-derived SiO2 membranes (#02 ~ 05) having different microporosity which Oyama et al [41,42,46,47] systematically synthesized by varying the organic ligand of starting Si alkoxide precursor and CVD process temperature in Ar: #02 [46] and #03 [41] (tetraethoxysilane (TEOS) at 600 • C), #04 (vinyltriethoxysilane (VTES) at 600 • C) [42], #05 (35% trimethylmethoxysilane (TMMOS) -TEOS at 650 • C) [47].…”
Section: Analysis Of Gas Permeation Behaviors (1) He and H2 Permeationsmentioning
confidence: 87%